How Physicians Learn to Say "I'm Sorry": Power, Culture, and Apology in Medical Education - Stephanie Quon; Sarah Low; Sarah Zhou; Katherine Zheng (Future of Medical Education Journal)
Background: Apologizing after a medical error is a vital component of ethical, patient-centered care. Sincere apologies can restore trust, reduce distress, and support healing. Yet the ability to apologize is not instinctive, it is shaped by institutional culture, power dynamics, and educational exposure. Despite increasing emphasis on disclosure training, no prior synthesis has thoroughly examined how medical students are taught to apologize or how sociocultural factors influence this learning. This scoping review explores how medical students learn to apologize in clinical settings, focusing on formal curricula, faculty role modeling, institutional norms, and emotional skill development.Method: Using Arksey and O’Malley’s framework, refined by Levac et al., and reported per PRISMA-ScR guidelines, we searched PubMed, MEDLINE, Scopus, ERIC, and Google Scholar. Peer-reviewed articles published in English from 2000-2024 were included if they addressed apology or error disclosure in undergraduate medical education. Two reviewers conducted independent screening and data extraction. Studies were thematically analyzed across five domains: curriculum, faculty role modeling, institutional culture, emotional skills, and outcomes.Results: Seventeen studies met inclusion criteria. Interventions such as simulations, communication frameworks, and patient safety exercises improved students’ confidence in disclosure. Faculty role modeling had strong influence, though observed apologies were often inadequate. Hidden curricula and hierarchies hindered authentic communication. Empathy training facilitated sincere apologies, yet few programs assessed long-term behaviors or addressed structural barriers.Conclusion: Teaching apology in medicine requires more than communication skills, it demands longitudinal, systems-based efforts that foster humility, transparency, and institutional accountability.